THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNIQUES IN SIMPLIFYING TAX ACCOUNTING PROCEDURES (World Economics and Finance Bulletin, 2024)
This research aims to simplify the work of intelligent technology to simplify the process of tax calculation in the tax administration as a company that provides many services to taxpayers. So that the administration is able to create new ideas to increase understanding and knowledge about how it takes care of taxpayers and strives to provide the right workplace, time, to create human relations and learning and learning, how that this is reflected in its tax efficiency to attract. new taxpayers and establish long-term relationships with them. To achieve this, the study is based on interviews as the main tool for collecting data and information for the analysis of its changes. The applied results showed a significant and positive impact of the intelligence technology in improving the tax accounting system, which is a good indicator of the impact of the intelligence technology in the performance of the General Tax Administration, the research sample.
Keywords: Artificial intelligence technology; tax records